If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(2/3)-4 (3/4)=1
We simplify the equation to the form, which is simple to understand
6(2/3)-4(3/4)=1
Reorder the terms in parentheses
+(+4)-4*( + 0.75)=1
Remove unnecessary parentheses
+4-4+*( + 0.75+)=+1
Reorder the terms in parentheses
+4+(-3)=1
Remove unnecessary parentheses
+4-3=+1
We move all terms containing to the left and all other terms to the right.
0=+1-4+3
We simplify left and right side of the equation.
0=0
0=0
This equation is an identity, so all real numbers are solutions.
| -12=r+12 | | 7x-1=5+4x | | -5.5n+0.56=1.64 | | 2(x+9)=2-(x-9) | | 5(z-18)-30=6 | | 180-x=46(90-x) | | 39=84w+39 | | 3(f-8)=33 | | 2x-5=x+9+5 | | -5+4(3-n)= | | y=ln(5x^3) | | 8d^2+30d+25=0 | | -3x+-10x-14=-12 | | (3n+6)(n-2)=0 | | 5-6=3.75 | | 2.8+7=4.8+89 | | 3x=9x-10 | | 42=3y+9 | | 7(-5x+3)=126 | | 7m+4(m-8)= | | log(x^5)-log(x^2)=3 | | -10(s+2)=48 | | 6(2x+4)=25x+250 | | A^2+4a=o | | 0.1(x-7)=3.5 | | y+(-10)=-2(x-5) | | p=6x+2 | | p=6x+1 | | 6789=4 | | -3x+6=x^2+8x+16 | | 0.4x-0.5(2x+3)=0.7(x+3) | | -(2x-4)-(8x-5)+14=-10x(x-1)-(5x+10)+3 |